Penggunaan Pompa celup tenaga Surya pada Perkebunan Semangka dan Melon Kelompok Tani Tunas Harapan dan Kelompok Tani Sappewalie Kelurahan Lalolang, Kecamatan Tanete Rilau Kabupaten Barru - M., A. Pananrangi; Safaruddin, Safaruddin; Masyitah, Masyitah (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to enhance irrigation efficiency in watermelon and melon farming through the application of solar-powered submersible pumps in Lalolang Village, Tanete Rilau District, Barru Regency. The activity was carried out in collaboration with the Tunas Harapan and Sappewalie Farmers’ Groups, focusing on the utilization of renewable energy to reduce dependence on conventional electricity and fossil fuels. The implementation methods included technology dissemination, training on pump operation and maintenance, and technical assistance throughout the planting period. The results indicated improvements in water distribution efficiency, reduced irrigation operational costs, and increased farmers’ understanding of solar energy technology. The adoption of solar-powered submersible pumps has proven to support sustainable agriculture, reduce carbon emissions, and increase crop productivity. This program is expected to serve as a model for the implementation of environmentally friendly technology in rural agricultural sectors.